Semi-Automatic Concept Map Generation Approach of Web-Based Kit-Build Concept Map Authoring Tool - Pinandito, Aryo; Prasetya, Didik Dwi; Hayashi, Yusuke; Hirashima, Tsukasa (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Apart from contributing to students’ learning outcomes, learning activities with digital concept maps were useful, fun, and engaging. Kit-Build concept map is a learning framework that incorporated concept map recomposition as its essential activity. It has been used to learn English as a Foreign Language (EFL) reading comprehension. Students learn through recomposing digital concept maps from a set of teacher’s concept map components; hence, the teacher’s concept map is essential in Kit-Build. A teacher’s concept map should reflect the learning context and strategy, the teacher’s purpose and intention, students’ understanding level, and focus questions. However, automatic-generated concept maps with Concept Map Mining (CMM) can only produce general concept maps that are not fit and difficult to correspond to said reasons. As teacher’s concept maps are essential in learning with Kit-Build, improving teachers’ productivity in composing concept maps of a particular learning material becomes necessary. This study proposed a semi-automatic concept map generation approach of EFL reading comprehension texts with CMM to assist teachers composed their concept maps. The proposed concept map generation approach was integrated into the current Kit-Build concept map authoring tool as an authoring support feature. The accuracy of the support feature in generating concept map components is presented in this research. The result suggested that the proposed authoring support tool is better used to refine a concept map.